Gender Differences in Consumers Perception of Neuromarketing: Empirical Research from Slovak Republic - Margareta NADANYIOVA; Lubica GAJANOVA; Jana MAJEROVA (Communications of International Proceedings, 2023)
Neuromarketing represents one of the strategies that a company can choose when creating effective advertising. It is a scientific discipline based on the combination of cognitive science and neuroscience included in marketing, focused on consumer emotions. With this type of research, it is possible to use several tools that help capture the reactions of consumers when looking at an advertisement. Neuromarketing can be used in marketing research focused on the differences in consumers decision-making based on demographic factors, such as gender. The gender of consumers also affects different perceptions of neuromarketing, but it still has lack of research, so there is still the space for deeper research. In this reason, the main aim of the paper is to determine the gender differences in consumers perception of neuromarketing. The most important sources for secondary data were scientific research, statistical databases, and published professional publications. To find out the perception of neuromarketing by consumers based on gender, a questionnaire survey was conducted through e-mail communication and social media. For determination the sample size, the base file representing number of populations older than 15 was obtained from demographic statistics of the Statistical Office of the Slovak Republic. For the processing of the survey data, the quantitative assessment method was applied. Based on the analysis and results of the questionnaire survey, it is obvious that there are some differences in consumers perception of neuromarketing based on their gender, especially in perceived benefits and threats of neuromarketing. Most women would participate in neuromarketing research, compared to almost half of men. These findings can lead to better understanding of the decision-making process of the target segments and implementation of appropriate neuromarketing research.
Keywords: neuromarketing; consumers; consumers perception; consumer behaviour; decision-making process